PENGARUH MOTIVASI KERJA, BEBAN KERJA DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT PIONIKA AUTOMOBIL - Celsyanes Cornelya; Wasiman (LPPM Universitas Putera Batam, 2024)
Increasing competition in the business world heightens the need for high-quality workforce that meets standards to support smooth operational processes of the company. The role played by skilled and reliable workforce is crucial in managing business and providing significant benefits to the company. This study aims to examine the extent to which job motivation, workload, and job stress influence employee performance at PT Pionika Automobil. A total of 112 active employees of PT Pionika Automobil were sampled using quantitative research method. The data analysis methods employed in this study include validity test, reliability test, classic assumption test, multiple linear regression test, coefficient of determination test, and hypothesis test. This research utilized SPSS (Statistical Product and Service Solution) version 26 as the data analysis tool. The research findings indicate that job motivation, workload, and job stress significantly influence employee performance. The coefficient of determination analysis results state that job motivation, workload, and job stress significantly influence employee performance by 61.3%. The remaining percentage is influenced by other variables not examined in this study.